Legal Analysis of Government Regulation Number 28 of 2024 Concerning Foreign Doctors' Workforce in Indonesia - Irawan, Tri Pamungkas Ippilianingrum; Miarsa, Fajar Rachmad Bi; Yahya, Dhofirul; Romadhon, Ahmad Heru (Dinasti Research, 2025)
Research purposes This focus on procedures in bring in doctor foreigners in Indonesia, and regulations doctor foreign For area remote areas in Indonesia. Research use type study legal normative with approach legislation . Research results This show that Procedure in bring in doctor foreigners in Indonesia based on Constitution immigration that is must have a valid visa the goal is to get sign sign in , and permission stay . As for the procedure Submission Permission Employing Foreign Workers including : submission of RPTKA , submission of Permission Employing Foreign Workers (IMTA), Compensation Fund Payment , IMTA Approval Process , ITAS Management , and Reporting and Monitoring . As for permission practice doctor the must equipped with a number of condition administration includes : SIP, SIK, STR, and IMTA. Regulations The Indonesian government in bring in doctor foreign Still Not yet it is said ready , where Not yet There is regulation special that regulates placement doctor foreign in the regions left behind . PP Health only arrange that power health foreign Can practicing in Indonesia based on request facility service health . With thus mechanism distribution doctor foreign the No proactive .